Monitoring and Controlling the Electron Dynamics in Helium with Isolated Attosecond Pulses - Gilbertson, Steve; Chini, Michael; Feng, Ximao; Khan, Sabih; Wu, Yi; Chang, Zenghu (My University, 2010)
Helium atoms in the presence of extreme ultraviolet light pulses can lose electrons through direct photoionization or through two-electron excitation followed by autoionization. Here we demonstrate that, by combining attosecond extreme ultraviolet pulses with near infrared femtosecond lasers, electron dynamics in helium autoionization can be not only monitored but also controlled. Furthermore, the interference between the two ionization channels was modified by the intense near infrared laser pulse. To the best of our knowledge, this is the first time that double excitation and autoionization were studied experimentally by using isolated attosecond pulses.